Domestic wastewater treatment and agricultural reuse progress and reporting challenges - Qadir, M.; Drechsel, Pay; Jones, E. R. (Springer, 2025)
Safely treated wastewater is critical to water-related sustainable development. With a focus on the domestic wastewater component of SDG 6.3, this study synthesized the latest country-level data on domestic wastewater generation and treatment, aggregated by geographic regions and income classifications, and subsequently addressed the challenges for monitoring safe water reuse (wastewater use). The data synthesis reveals that the domestic sector generates 267.5 billion m3 yr− 1 of wastewater globally, of which 63% (168.8 billion m3 yr− 1) is collected in sewers and septic tanks, and 54.7% (146.3 billion m3 yr− 1) is treated. In comparison, 45.3% (121.2 billion m3 yr− 1) is released to the environment in untreated form, either uncollected (98.7 billion m3 yr− 1) or collected but untreated (22.5 billion m3 yr− 1). Although these data, compiled by the World Health Organization (WHO), show progress in view of SDG 6.3.1, the proportion of safely treated wastewater remains strongly uneven between geographic regions and income groups. On the water reuse front, while there is significant progress in industrial (e.g. China) and agricultural (e.g. Egypt) reuse of treated wastewater, untreated water reuse remains a dilemma that requires special attention where it is most common, i.e., in low-income and lower-middle-income countries. Considerable challenges in assessing the state-of-affairs remain because of its terminology, informal status and the limited availability (and usefulness) of reported reuse volumes or areas for WHO’s health-based targets.